Measuring the impact of slow zones on street life using social media. (December 2022) - Salazar-Miranda, Arianna; Heine, Cate; Duarte, Fabio; Schechtner, Katja; Ratti, Carlo
Abstract: Streets are fundamental to social and economic exchange in cities. Despite their importance for urban life, streets continue to dedicate more space to cars than people, raising concerns about their ability to host social exchange. In this paper, we study the extent to which slow zones (areas designed to be more pedestrian-friendly via speed limit reductions) affect human activity in streets. We study this question in the context of Paris, which implemented several slow zones covering a large portion of the city between 2010 and 2019. We exploit differences in the effects of the policy at the boundaries of the slow zones and their staggered introduction over time to identify their causal effect on human activity. Comparing street segments immediately within the slow zone boundary (our treatment group) to street segments immediately outside the slow zone (our control group) shows that human activity measured using Twitter is 44% higher in slow zones. This effect is driven by an increase in both the number of users and in the number of tweets per user, suggesting that slow zones attract more people and that people are tweeting more in these areas. We also show that slow zones draw visitors from a wider geographic range of neighborhoods, contributing to social mixing. Highlights: We use Twitter data to study the impact of slow zones (areas where speed limits are reduced) on human activity on streets. We identify a causal effect by exploiting slow zones' discrete boundaries and their staggered introduction over time. Slow zones saw increases in human activity and attracted individuals from a broader range of Paris neighborhoods.